Pengaruh Pengetahuan, Resiko Dan Motivasi Investasi Terhadap Minat Mahasiswa Ekonomi Untuk Berinvestasi Di Pasar Modal: (Studi Kasus Mahasiswa Fakultas Ekonomi, Bisnis Dan Pariwisata Universitas Hindu Indonesia) - Ni Wayan Koni Mariati; Ni Komang Sumadi; Ni Putu Yeni Yuliantari (UNHI Press, 2025)
Academics and the general public alike are looking to the financial markets for investment opportunities in this age of rapid technical development and globalization. Given their position as the nation's future leaders, students must have a solid grasp of investments in order to secure a more prosperous future. Students of economics at Hindu University of Indonesia had their interest in investing in the capital markets studied, and the effects of investment knowledge, risk, and motivation were examined. The research employs a quantitative method and aims to gather data from undergraduates enrolled in the management and accounting disciplines. After using stratified random sampling and the Slovin technique, 94 respondents were selected for the study. Data was gathered via Likert-scale questionnaires. Using SPSS 24.0's multiple linear regression analysis, we found that students' interest in capital market investing is favorably and substantially impacted by investment knowledge, risk exposure, and motivation.